Effectiveness and adverse events of topical and allergen immunotherapy for atopic dermatitis: a systematic review and network meta-analysis protocol (2020)
ABSTRACT: Background: Atopic dermatitis (AD) is an inflammatory chronic condition that affects the skin of children and adults and has an important impact on the quality of life. Treatments for AD are based on environmental controls, topical and systemic therapies, and allergen-specific immunotherapy (AIT). However, it remains unclear the effectiveness and adverse events of AIT and all conventional topical treatments compared with placebo and each other for AD. Methods: We will search five electronic databases [Central Cochrane register of controlled trials (CENTRAL), MEDLINE, EMBASE, CINAHL, and LILACS] from inception until November 2019 with no language restriction, and we will include experimental studies [randomized controlled trials (RCTs), and quasi-RCTs]. The primary outcome is global and specific skin symptoms assessment. Secondary outcomes are hospital length of stay, quality of life, and adverse events. Reviewers independently will extract data from the studies that meet our inclusion criteria and will assess the risk of bias of individual primary studies. We will conduct random effects pairwise meta-analyses for the observed pairwise comparisons with at least two trials. Then, we will perform random-effects Bayesian network meta-analysis (NMA) to obtain treatment effects for all possible comparisons and to provide a hierarchy of all interventions for each outcome. Possible incoherence between direct and indirect sources of evidence will be investigated locally (if possible) and globally. To investigate sources of statistical heterogeneity, we will perform a series of meta-regression analyses based on pre-specified important effect modifiers. Two authors will appraise the certainty of the evidence for each outcome applying the GRADE's framework for NMA. Discussion: The findings of this systematic review will shed the light on the effectiveness and adverse events of all possible comparisons for treating AD and on the quality of the collated evidence for recommendations. It will also provide critical information to health care professionals to comprehend and manage this disease at different age stages, treatment type, duration, and severity of atopic dermatitis. Systematic review registration: PROSPERO Protocol ID CRD42019147106. Keywords: Atopic dermatitis; GRADE approach; Immunotherapy; Systematic review, Meta-analysis, Network meta-analysis; Topical administration.